Identification of I‐7 expands the repertoire of genes for resistance to Fusarium wilt in tomato to three resistance gene classes. (18th September 2015) - Gonzalez‐Cendales, Yvonne; Catanzariti, Ann‐Maree; Baker, Barbara; Mcgrath, Des J.; Jones, David A.
Summary: The tomato I ‐3 and I ‐7 genes confer resistance to F usarium oxysporum f. sp. lycopersici ( F ol ) race 3 and were introgressed into the cultivated tomato, S olanum lycopersicum, from the wild relative S olanum pennellii . I‐3 has been identified previously on chromosome 7 and encodes an S‐receptor‐like kinase, but little is known about I ‐7 . Molecular markers have been developed for the marker‐assisted breeding of I ‐3, but none are available for I ‐7. We used an RNA‐seq and single nucleotide polymorphism (SNP) analysis approach to map I ‐7 to a small introgression of S . pennellii DNA ( c . 210 kb) on chromosome 8, and identified I ‐7 as a gene encoding a leucine‐rich repeat receptor‐like protein (LRR‐RLP), thereby expanding the repertoire of resistance protein classes conferring resistance to F ol . Using an eds1 mutant of tomato, we showed that I‐7, like many other LRR‐RLPs conferring pathogen resistance in tomato, is EDS1 (Enhanced Disease Susceptibility 1) dependent. Using transgenic tomato plants carrying only the I ‐7 gene for F ol resistance, we found that I ‐7 also confers resistance to F ol races 1 and 2. Given that F ol race 1 carries A vr1, resistance to F ol race 1 indicates that I‐7‐mediated resistance, unlike I‐2‐ or I‐3‐mediated resistance, is not suppressed by Avr1. This suggests that Avr1 is not a general suppressor of F ol resistance in tomato, leading us to hypothesize that Avr1 may be acting against an EDS1‐independent pathway for resistance activation. The identification of I ‐7 has allowed us to develop molecular markers for marker‐assisted breeding of both genes currently known to confer F ol race 3 resistance ( I ‐3 and I ‐7 ). Given that I‐7‐mediated resistance is not suppressed by Avr1, I ‐7 may be a useful addition to I ‐3 in the tomato breeder's toolbox.